1992
DOI: 10.1007/bf01249288
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific interference for nest sites betweenLeptothorax congruus andMonomorium intrudens

Abstract: SummaryInterference competition for nest sites was studied in ant communities dominated by Leptothorax congruus in the suburbs of Tokyo, central Japan. At the two study plots located in a deciduous wood and in grassland, L. eongruus constructed nests in dead branches or stems of dead grasses. Approximately 50 % of the nests were physically broken within a year, suggesting that they were very fragile. Of totals of 67 and 91 nests ofL. congruus marked at the two sites, 12 (17.5 %) and 53 (58.2 %) nests, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Further, litter ant colonies never appear to achieve the permanence of many large soil nesting species. Nests of twigs and leaves are fragile and temporary, subject to predation and disturbance (Yamaguchi 1992), forcing litter colonies to move periodically (Byrne 1994;Herbers 1986;Ward 1981). Life for a litter ant colony may be more unpredictable than for their large soil nesting counterparts.…”
Section: Caste Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, litter ant colonies never appear to achieve the permanence of many large soil nesting species. Nests of twigs and leaves are fragile and temporary, subject to predation and disturbance (Yamaguchi 1992), forcing litter colonies to move periodically (Byrne 1994;Herbers 1986;Ward 1981). Life for a litter ant colony may be more unpredictable than for their large soil nesting counterparts.…”
Section: Caste Allocationmentioning
confidence: 99%
“…If litter Pheidole occupy small, breakable nests, making colonies vulnerable to predators and random catastrophe (Byrne 1994;Herbers 1986;Yamaguchi 1992), then colonies may be perishing before reaching a size where resources limit colony growth.…”
Section: Plant Defense Theory and Caste Ecologymentioning
confidence: 99%
“…Many studies, which have investigated niche partitioning in ant communities, revealed that competition can result: (1) in direct antagonistic behaviour (Savolainen and Vepsäläinen 1988;Yamaguchi 1992;Retana and Cerdµ 1995;Punttila et al 1996;, (2) in temporal segregation (Baroni Urbani and Aktaç 1981;Marsh 1988;Fellers 1989;Deffernez et al 1990;Cros et al 1997;de Biseau et al 1997;Retana and Cerdµ 2000;Albrecht and Gotelli 2001;Campos and Schoereder 2001), (3) in spatial segregation by microhabitat differentiation (Punttila et al 1996, Johnson 2000, or (4) in different foraging strategies (Traniello 1983(Traniello , 1987Jones and Sherman 1990;Perfecto 1994;de Biseau et al 1997;Sanders and Gordon 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of ants have highlighted the importance of both intraspecific and interspecific competition in structuring communities (Cerdá et al 1998;Eldridge and Traniello 1981;Fox et al 1985;Holway 1999;Human and Gordon 1999;Passera et al 1996;Perfecto 1994;Punttila et al 1994;Savolainen 1990;Yamaguchi 1992). Competitive ability is important because the resource requirements of many ant species overlap substantially (Pisarski and Vepsä lä inen 1989), not just between closely-related species but also between distantly-related species (Mabelis 1984).…”
Section: Introductionmentioning
confidence: 97%